United Nation Interim Administration for Kosovo (UNMIK): Pengaruh Organisasi Internasional PBB Terhadap Pembentukan Pemerintahdi Kosovo - Kristiningrum, Nur Dwi (Global and Policy Journal of International Relations, 2014)
ABSTRACTKosovo has a long way to achieve its independence. The struggle of territory between ethnic Albanians in Kosovo with Serbs has led to occurrence of violent conflict. In 1999 NATO intervention to stop the conflict. After NATO has bombing Kosovo, United Nation form Kosovo yaitu United Nations Interim Administration Mission in Kosovo (UNMIK) to maintain peace and security. However, UNMIK is not only create peacekeeping, but extends to participate in composing and arranging the government in Kosovo. According to Johan Galtung’s theory, UNMIK has been able to resolve the conflict in Kosovo. The theory include peacekeeping, peacemaking, and peacebuilding. In addition, UNMIK has given its influence in the formation of independent.Keywords: pramodialist approach, peacekeeping, state-building theory.DOI:https://doi.org/10.33005/jgp.v2i01.1985